(untitled) (Acta Entomologica Serbica, 2022)
During project field activities conducted in May 2021 in the territory of the Landscape of Outstanding Features “Dolina Pčinje” at the locality Vogance, one dead and trampled specimen of the web-spinning sawfly Caenolyda reticulata (Linnaeus, 1758) was found. The new finding is the first report of the species from Serbia, as well as from the Balkans, and significantly expands its known distribution into southeast Europe. The host plants of this species are pines (Pinus spp.), of which black pine (Pinus nigra subsp. nigra) occurs in the Pčinja River valley.